Business Model Innovation for IoT Solutions: An Exploratory Study of Strategic Factors and Expected Outcomes - Florin Sabin Foltean; Bogdana Glovațchi (Amfiteatru Economic)
Business model innovation is a key success factor for IT companies competing in technologically uncertain environments. Despite the need of IoT solution developers to renew their business models to effectively create value for customers and capture value for the company, the strategic factors of business model innovation for IoT solutions have remained under-researched so far. The paper addresses this knowledge gap by exploring the strategic factors of business model innovation and its results from the perspective of RBV (Resource-Based View) theory. The theoretical foundation of this research is based on the literature of the business model innovation and the strategic marketing literature. In the empirical exploration of the strategic factors of the business model innovation, we adopted a qualitative research strategy having as methodological basis Grounded theory. More precisely, we conducted 12 semi-structured interviews with top managers at IT companies operating in Romania that have successfully developed IoT solutions. Proactive market orientation, technology orientation, entrepreneurial orientation, and adaptive marketing capabilities have been identified as strategic factors of business model innovation for IoT solutions, while competitive advantage and customer satisfaction as the main expected outcomes